Mixed convective non-linear radiative flow with TiO2-Cu-water hybrid nanomaterials and induced magnetic field. Issue 8 (5th August 2019) - Ahmad Khan, Sohail; Khan, Muhammad Ijaz; Hayat, Tasawar; Faisal Javed, Muhammad; Alsaedi, Ahmed
Abstract : Purpose: The purpose of this paper is to address the impact of induced magnetic field in mixed convective stagnation flow of TiO2 -Cu -water hybrid nanofluid towards a stretchable sheet. Non-linear thermal radiation and heat source/sink are accounted. Flow of hybrid nanofluid is discussed. Non-linear partial differential expressions are converted to ordinary ones through appropriate transformations. Design/methodology/approach: The obtained systems are solved for convergence solutions via homotopy analysis method. Graphical results are discussed for different physical variables on the velocity, induced magnetic field and temperature fields for both Cu water nanofluid and TiO2 -Cu -water hybrid nanofluid. Finally, the effect of different physical variables on skin friction coefficient ( Cfx ) and Nusselt number Nux in the presence of water nanofluid and TiO2 -Cu -water hybrid nanofluid are discussed. Findings: Velocities and induced magnetic field are increasing functions of mixed convection parameter and nanoparticle volume fraction. Temperature rises for higher radiation parameter. Skin friction is greater in case of Cu-water nanoliquid, while Nusselt number is less for Cu-water nanofluid when they are compared with hybrid nanoliquid TiO2 -Cu -water. Originality/value: No such work is not yet present in the literature.